Determining the mechanism by which PZA exerts its antimycobacterial activity against Mycobacterium tuberculosis - Dillon, Nicholas (My University, 2017)
Pyrazinamide (PZA) is one of the four first line drugs used to treat Mycobacterium tuberculosis infections. For PZA to be active against M. tuberculosis the drug must be enzymatically converted into pyrazinoic acid (POA) by the M. tuberculosis amidase PncA. In vitro PZA susceptibility requires concurrent exposure to stress, potentially linking the extracellular environment of M. tuberculosis to the drug’s mechanism of action. While the production of POA is required, its molecular target is unknown. Multiple models have been proposed to explain the anti-mycobacterial activity of POA, yet, confirmatory evidence is required for their validation. We evaluated each of the proposed models to assess their validity. Our findings refute the previously proposed models leading us to conclude that the mechanism of action of PZA was still undefined. While studying drug susceptibility in a pantothenate auxotrophic strain of M. tuberculosis we discovered that supplementation with metabolites of the pantothenate/coenzyme A pathway antagonized the activity of PZA. In further characterization of this phenomenon, we found that some metabolic precursors to pantothenate also antagonized PZA only when the precursors could be used for the synthesis of pantothenate. Based on the recent identification of a novel PZA resistance mutation we set out to use a library of transposon mutagenized M. tuberculosis to select for PZA resistance. To our surprise, we identified transposon insertions in over 150 genes that had no previous association with PZA resistance. Compiling a list of the most frequent genomic positions that contained the transposon we uncovered a relationship between PZA susceptibility and the sigma factor E (SigE) regulon. SigE activation in M. tuberculosis occurs in response to extracyotplasmic stress. When examining the impact of extracyotplasmic stress on PZA activity we found that POA worked synergistically with H2O2 against M. tuberculosis. Based on our studies we hypothesize that the synergy occurs through increased hydroxyl radical production from the interaction of POA and iron complexes with H2O2. Increasing cellular oxidative stress would negatively impact multiple metabolic processes and could lead to a reduction in free coenzyme A (CoA). A recent study found a reduction in CoA levels after PZA treatment further linking the drug to this crucial cofactor. Combining our data we hypothesize that POA reduces free CoA availability through increased oxidative stress, leading to the eventual killing of M. tuberculosis through an inhibition of global metabolic functions.
University of Minnesota Ph.D. dissertation. February 2017. Major: Microbiology, Immunology and Cancer Biology. Advisor: Anthony Baughn. 1 computer file (PDF); ix, 161 pages.